The Role of Trust as a Mediator of Web Quality Perception, Risk, Reputation on The Intention to Repurchase Garuda Indonesia Ticket Online - Wijoseno, Aryo; Hartono, Sri (Dinasti Publisher, 2025)
This study seeks to empirically investigate the factors influencing online repurchase intention for Garuda Indonesia's domestic airline tickets, with trust serving as a mediating variable. The study encompassed 201 participants, predominantly Millennials and Gen Z, who acquired tickets through Garuda Indonesia's official website or online travel agencies (OTAs). Data were analyzed with PLS-SEM. The results indicate that performance expectancy, information quality, perceived ease of use, and reputation have a favorable and significant effect on online repurchase intention. Trust also positively affects online repurchase intention. Nonetheless, trust does not facilitate the connections between design quality and perceived risk regarding online repurchase intention. Furthermore, design quality and perceived risk exhibit no significant direct consequences. These insights provide strategic implications for improving the effectiveness, efficiency, and competitiveness of Garuda Indonesia's digital platforms in the local market.